RELATIONSHIP BETWEEN SUPPLEMENTARY FOODS AND HISTORY OF INFECTIVE DISEASE TO STUNTING EVENTS IN CHILDREN IN SIKUMANA PUBLIC HEALTH ,CENTER KUPANG CITY - asyah nur (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
Stunting or shortness is a condition of failure to thrive in infants (0-11 months) and children under five (12-59) months. Giving MP-ASI that is not in accordance with the age and needs of the baby can have an impact on the health and nutritional status of the baby, the average child who has an infection will certainly experience a decrease in appetite, this can also be a risk factor for stunting. The purpose of this study was to analyze the relationship between complementary feeding and a history of infectious disease to the incidence of stunting in children under five at the Sikumana Community Health Center, Kupang City. The research design used in this study was a cross sectional. The population in this study were all stunting toddlers in Fatukoa Village. Sampling with purposive sampling technique. Data collection in this study used primary and secondary data. The data collection tool is a questionnaire sheet. Data analysis used univariate and bivariate using Spearman Rank test. The results showed a P value of 0.000, on the complementary feeding variable and a P value of 0.000, on the variable history of infectious diseases. So it was concluded that there was a relationship between the provision of complementary feeding and a history of infectious disease incidence of stunting in toddlers at the Sikumana Health Center, Kupang City.